Correction: A bright NIR-II fluorescent probe for breast carcinoma imaging and image-guided surgery. Issue 99 (28th November 2019) - Zeng, Xiaodong; Xue, Liru; Chen, Deliang; Li, Shanshan; Nong, Jinxia; Wang, Bo; Tang, Lin; Li, Qianqian; Li, Yang; Deng, Zixin; Hong, Xuechuan; Wu, Mingfu; et al.
Abstract : Correction for 'A bright NIR-II fluorescent probe for breast carcinoma imaging and image-guided surgery' by Xiaodong Zeng et al., Chem. Commun., 2019, DOI: ; 10.1039/c9cc07694h .